The Marriage Traditions of the Parmalim Community as Inspiration for Painting Creation - Simbolon, Jollin Josep; Tarigan, Nelson (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
Indonesia is renowned for its rich cultural heritage and diverse beliefs, one of which is Ugamo Malim, a tradition embraced by the Parmalim community of the Batak tribe. The wedding customs of the Parmalim, particularly in Sianjur Mula-Mula, preserve ancestral rituals that diverge significantly from those of Christian or Islamic Batak communities. This research investigates how the Parmalim wedding tradition, particularly its symbolic six-movement ceremonial dance, can inspire the creation of painting artworks. The study aims to delve into the cultural significance of these traditions, enhance appreciation for the beauty of Parmalim’s heritage, and promote the preservation and celebration of Indonesia’s cultural diversity. The creative process employed a structured methodology comprising preparation, elaboration, contemplation, and realization to develop meaningful and impactful artworks. Utilizing bravura and chiaroscuro techniques, the artist produced twelve paintings inspired by Parmalim’s wedding traditions, each capturing symbolic elements such as “Hohom,” representing gentleness, and “Mangurdot Somba,” reflecting joy. However, this article presents only three of these paintings, focusing on their symbolic elements and artistic interpretation. These works demonstrate a fusion of traditional themes and creative expression, employing freely chosen materials and tools on sketched canvases to achieve optimal visualization and proportionality. The study concludes that creating paintings based on Parmalim wedding traditions not only showcases artistic prowess but also serves as an act of cultural appreciation and preservation. This body of work underscores the profound connection between art and cultural identity, reinforcing the significance of valuing Batak heritage and fostering cultural diversity.